Analisis peran kredit investasi terhadap pertumbuhan ekonomi di Indonesia - Saskya Octarina, Amalinda; Khoirudin, Rifki (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
This study aims to analyze the role of investment credit in banking on economic growth. This study uses several variables, such as: investment credit, inflation, human development index, and central bank interest rates. The time span used in this study is thirty-one years from 1990-2020. This study uses quantitative methods. Based on the results of data analysis, it is concluded that the inflation variable, human development index, and the central bank interest rate together have a significant effect on the economic growth variable, while the investment credit variable has no significant effect on the economic growth variable. The coefficient of determination (adjusted R2) shows that the effect of investment credit, inflation, development index and central bank interest rate in explaining the role of investment credit is 0.8140, while the remaining 18.60% is affected by other variables not included in the study.